Leaching characteristics of biomass ash-based binder in neutral and acidic media. (July 2019) - Chaunsali, Piyush; Uvegi, Hugo; Traynor, Brian; Olivetti, Elsa
Abstract: Biomass ash results from the combustion of agricultural residues, which, in many developing countries, are a primary source of power generation for small and medium size industries. This study focuses on the performance of a binder synthesized from an Indian biomass ash, Indo-Gangetic clay, hydrated lime, and aqueous 1M NaOH solution. To measure the extent of leaching and its impact on physicochemical properties, the biomass ash binder in powder form (<45 μm size) was exposed to two different leaching media: deionized water and 0.1M HNO3 at two different solution-to-sample ratios (by wt.) of 10 and 100. Sodium leaching was found to be prominent in the biomass ash binder irrespective of leaching medium and solution-to-sample ratio. However, calcium leaching was significantly higher in 0.1M HNO3 than in deionized water. Calcium silicate hydrate present in the biomass ash binder was found to be less chemically stable in 0.1M HNO3, exhibiting complete calcium leaching at a solution-to-sample ratio of 100. Furthermore, significant leaching of calcium in 0.1M HNO3 solution resulted in phase modification of calcium silicate hydrate, the main reaction product of the biomass ash binder.